THE EFFECTIVENESS OF LEARNING MODEL BASED DIGITAL STORYTELLING TO IMPROVE STUDENTS' EMOTIONAL INTELLIGENCE - Sulistianingsih, Endang (Universitas Negeri Semarang, 2017)
This study was an experimental research with true experimental design. which aimed at describing the effectiveness of digital storytelling on studentsâ€™ emotional intelligence. The object of this research was students of third and fourth elementary school. This research conducted in three elementary schools in Tegal regency. The collecting data technique was observation and questionnaire. Hypothesis testing used was t-test. The research instruments were tested by validity and reliability test. It is concluded that digital storytelling is effective as a learning model to improve studentsâ€™ emotional intelligence.Â